A conceptual model of downstream supply chain and the importance of it in Bangladesh Jute Industry - Ashif, Mehedi Ahsan (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.